Pengaruh Hubungan antar Manusia dan Kondisi Lingkungan Kerja terhadap Etos Kerja pada Pegawai Kantor Camat Batin XXIV Kabupaten Batang Hari - Siswati, Etty; Khoiroh, Nadiatul; Kosasi, Niki; Fauzani, Evi; Narulita, Sari (Universitas Batanghari Jambi, 2024)
The aim of this thorough is to clarification the impact of human relations, working environment and employee behavior on society on Kantor Camat Batin XXIV Kabupaten Batang Hari. A comprehensive analysis method uses a number of background analysis tools. Measurement of the variable Human Relations (X1), Working Environment (X2) and Employee Behavior (Y) as dependent variable was carried out using t- and F-test. The aim of partial thorough (t test) is that the t-value of human relations 8,670 from the t table number 1,649. This through explain that human relations have an impact to employee behavior on society at batin XXIV District Head Office. Working Environmental Conditions, result of t-count value 3,321. The t-table number is 1,649. With an impact on employee’s behavior on District Camat Batin XXIV Batang Hari Regency. Training, inter-human relations, work environment conditions simultaneously (F Test) obtained Fcount 78.533 > Ftable is 2.90, which means that Human Relations (X1), Working Environment (X2) have a positive impact simultaneously to Employee Behavior on Camat Batin XXIV Batang Hari Regency.The resulting adjust R squere is equal to 83.3 %. Therefore, we can confirm that the percentage change between Human Relationship, Working Environment and employee Behavior on District Camat Batin XXIV Batang Hari Regency.